2017
DOI: 10.1063/1.4980170
|View full text |Cite
|
Sign up to set email alerts
|

On the distribution of oxide defect levels in Al2O3 and HfO2 high-k dielectrics deposited on InGaAs metal-oxide-semiconductor devices studied by capacitance-voltage hysteresis

Abstract: In this work, we study oxide defects in various III-V/high-k metal-oxide-semiconductor (MOS) stacks. We show that the choice of a given starting measurement voltage with respect to the MOS flat-band voltage affects the observed capacitance-voltage hysteresis. We discuss how this behavior can be used to study the distribution of oxide defect levels. With the help of comprehensive experimental data, we show that Al2O3 and HfO2 have different hysteresis characteristics related to different oxide defect distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…Hysteresis width Δ fb = 2.1 V is obtained for sweeping between −5 V and +10 V, Δ fb = 2.0 V is obtained for sweeping between −5 V and +5 V, and Δ fb = 1.2 V is obtained for sweeping between −5 V and +3 V. Above values are consistent with the literature results obtained for Al 2 O 3 /HfO 2 stacks on In 0.53 Ga 0.47 As [25]. Namely, in [25] it is observed that there is a maximum value of Δ fb between the two Al 2 O 3 /HfO 2 thicknesses ratios of 2.5 nm/3.0 nm and 0.5 nm/2.5 nm higher than or equal to 0.4 V. From our experiment a higher value of 1.2 V is obtained for the thicknesses ratio 1.0 nm/2.5 nm.…”
Section: − Hysteresissupporting
confidence: 91%
See 1 more Smart Citation
“…Hysteresis width Δ fb = 2.1 V is obtained for sweeping between −5 V and +10 V, Δ fb = 2.0 V is obtained for sweeping between −5 V and +5 V, and Δ fb = 1.2 V is obtained for sweeping between −5 V and +3 V. Above values are consistent with the literature results obtained for Al 2 O 3 /HfO 2 stacks on In 0.53 Ga 0.47 As [25]. Namely, in [25] it is observed that there is a maximum value of Δ fb between the two Al 2 O 3 /HfO 2 thicknesses ratios of 2.5 nm/3.0 nm and 0.5 nm/2.5 nm higher than or equal to 0.4 V. From our experiment a higher value of 1.2 V is obtained for the thicknesses ratio 1.0 nm/2.5 nm.…”
Section: − Hysteresissupporting
confidence: 91%
“…Namely, in [25] it is observed that there is a maximum value of Δ fb between the two Al 2 O 3 /HfO 2 thicknesses ratios of 2.5 nm/3.0 nm and 0.5 nm/2.5 nm higher than or equal to 0.4 V. From our experiment a higher value of 1.2 V is obtained for the thicknesses ratio 1.0 nm/2.5 nm. This value is substantially higher than the value reported for pure HfO 2 [26] under similar conditions.…”
Section: − Hysteresissupporting
confidence: 54%
“…39 The MFCV characteristics of the samples are largely consistent with the previous work by Tang et al 21 and those reported in the literature. [11][12][13][14][15]19,20,29 Significant frequency dispersion can be observed from inversion into accumulation. Dispersion in such regions can be explained by the interface traps inside the bandgap 32,40 and the response of border traps, 3,12,14,16 respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, oxide defects are also accounted for the hysteresis observed on C-V sweeps in trace back mode, and special attention has been drawn toward the energy and spatial distribution of such defects. [18][19][20][21] Surface treatments such as sulfur passivation, 22,23 nitridation, 24 As 2 capping and decapping, [25][26][27][28] hydrogen, 29 oxygen, 30,31 and forming gas anneals (FGA) 21, 23,32,33 have shown diverse levels of success in the passivation of D it and BTs, resulting in different values for the capacitance dispersion with frequency. Dependences on fabrication process have been also observed on the widths of the loops during C-V hysteresis sweeps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation